USM, TORAY TO STRENGTHEN ACADEMIA-INDUSTRY LINKAGES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 7 December 2016 President of Toray Industries Inc., Dato' Akihiro Nikkaku today received his Honorary Doctor of Engineering degree from the Universiti Sains Malaysia (USM) ProChancellor, Tan Sri Datuk Mustafa Mansur in a simple yet meaningful ceremony held here.